Effects of Low Temperature on Shrimp and Crab Physiology, Behavior, and Growth: A Review - Ren, Xianyun; Wang, Qiong; Shao, Huixin; Xu, Yao; Liu, Ping; Li, Jian (Frontiers in Marine Science, 2021)
As important aquaculture species worldwide, shrimps and crabs are thermophilic animals with a feeble thermoregulation ability. Changes in environmental factors are the main reason for the decrease in the immunity and disease resistance ability of cultured organisms. Water temperature is one of the most common abiotic stress factors for aquatic ectotherms. It influences nearly all biochemical and physiological processes in crustaceans, resulting in an imbalance in ion and water homeostasis, neuromuscular function loss, cellular dehydration, and altered metabolic pathways. The present review summarizes the current knowledge on the effects of low temperature on the physiological response, and the behavior, development, and growth of shrimp and crab. We suggest a deeper research to understand the physiological processes involved in thermoregulation; this knowledge could be used to reduce the adverse effects in the shrimps and crabs during the culture.